PEMILIHAN PORTOFOLIO CRYPTOCURRENCY: (BITCOIN, YEARN.FINANCE, DOGECOIN, BINANCE COIN, CARDANO, DAN MONERO) - Anatasya Pratiwi Putri; Raja Ria Yusnita; Raja Ade Fitrasari Mochtar (Bisnis-Net, 2023)
Â Cryptocurrency is a digital currency that can be used for transaction tools, using cryptography so that it is difficult to counterfeit. The crypto does not have a physical form, but can still be used as a digital asset. This study aims to determine an efficient portfolio of several cryptocurrencies by forming an Efficient Frontier Line. The efficient frontier line is formed by determining the risk and return of 6 cryptocurrencies, namely Bitcoin, Dogecoin, Yearn.finance, Binance Coin, Monero and Cardano. The technique used to select the sample is direct observation or observation of the prices of 6 cryptocurrencies for the period January-December 2021. In addition, literature studies through journals, news related to cryptocurrencies are also used. To form an efficient portfolio model, this study uses quantitative and qualitative analysis. The result of this study is that there are investment options for investors who like risk, choosing the proportion that maximizes profits with high risk. For investors who do not like high risk, they can choose the minimum proportion, and for moderate investors who can accept the risk of an equal proportion can choose a random proportion. Based on the results of the 3 proportions that will be chosen by investors, Bitcoin is one of the cryptocurrencies that is always chosen to invest because Bitcoin is a crypto that produces efficient returns and risks even though the risk in Bitcoin is quite high at certain returns.Keywords: Cryptocurrency, Risk, Return